2021
DOI: 10.2196/23147
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Prolonged Length of Hospital Stay After Cancer Surgery Using Machine Learning on Electronic Health Records: Retrospective Cross-sectional Study

Abstract: Background Postoperative length of stay is a key indicator in the management of medical resources and an indirect predictor of the incidence of surgical complications and the degree of recovery of the patient after cancer surgery. Recently, machine learning has been used to predict complex medical outcomes, such as prolonged length of hospital stay, using extensive medical information. Objective The objective of this study was to develop a prediction mo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 25 publications
1
24
0
Order By: Relevance
“…We found that PPLOS was more likely in patients undergoing Mile's operation and left hemicolectomy than in those undergoing other surgical approaches. This might be related to more complex surgical procedures and greater trauma in these two surgical approaches compared with other surgical approaches [14,16]. We found that tumor metastasis was a protective factor against PPLOS.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…We found that PPLOS was more likely in patients undergoing Mile's operation and left hemicolectomy than in those undergoing other surgical approaches. This might be related to more complex surgical procedures and greater trauma in these two surgical approaches compared with other surgical approaches [14,16]. We found that tumor metastasis was a protective factor against PPLOS.…”
Section: Discussionmentioning
confidence: 85%
“…However, multivariate analysis found that other factors were also related to PPLOS. These results indicated that PPLOS was the result of a combination of surgical factors and multiple factors [13,14]. Herein, variables related to anesthesia management, such as intraoperative lung-protective ventilation, urine volume, and lactic acid level, were not found to be related to PPLOS.…”
Section: Discussionmentioning
confidence: 90%
“…They can be reproduced with machine learning, where multifactorial prediction models for 30-day mortality and length of stay have an area under the receiver operating characteristic curve (AUC) of [0.8 for some cancer surgeries. 8 Methodological excellence is apparent in the current study by Aquina et al, where additional risk adjustment, controlling for patient demographics, comorbidity status, tumor characteristics, and pathological stage, was undertaken because of evidence of residual confounding on bivariate analysis of patient and oncologic factors by adjusted hospital TOO rate quintile. While this additional adjustment controls for those factors captured in the NCDB data, it still falls short of acknowledging the complexity of technical, social, and biological factors that have all been correlated to cancer outcomes.…”
mentioning
confidence: 89%
“…Those for mortality, hospital length of stay, and intermediate outcomes including acute kidney injury, deep venous thrombosis, re-intubation, and delirium, among others, have all been developed. [11][12][13][14] Models predicting which patients require therapy, and the effect of treatment, have more recently been reported as well as those predicting adverse events. 15,16 Perhaps the best example is intraoperative hypotension, a common adverse event with a clear relationship to multiple organ system injuries.…”
Section: Machine Learning (Ml) and Predictive Analyticsmentioning
confidence: 99%